ECONOMIC DETERMINANTS OF CRIME TRENDS IN KENYA - Mogeni, Evans Geoffrey (My University, 2011)
The paper was intended to establish the major economic causes of crime upsurge in Kenya by using the Johansen Cointegration and VEC model, using annual data from 1975-2012 of gross per capita income, public expenditure on law, order, and safety, consumer price index, and Conviction. The time series stationary properties of the data were examined through the use of augmented dickey-Fuller (ADF) test.We established the existence of negative significant long run Relationship between crime and GDP per capita. Convictions also had negative and significant relationship with crime. Public expenditure on safety, law and order (PSLO) had positive relationship with crime. Short run Granger causality was established running from Public expenditure on safety, law and order (PSLO) to crime in Kenya